Protective Effects of Oxyberberine in 5-Fluorouracil-Induced Intestinal Mucositis in the Mice Model. (30th May 2022) - Huang, Ronglei; Ai, Gaoxiang; Zhong, Linjiang; Mai, Liting; Chen, Jian-Nan; Liu, Yuhong; Li, Yucui; Huang, Xiaoqi; Su, Ziren; Zhan, Janis Ya-Xian
Abstract : Berberine (BBR), a major active constituent of Rhizoma coptidis, was reported to exert beneficial effects on intestinal mucositis (IM) induced by 5-fluorouracil (5-FU). However, the bioavailability of BBR is extremely low, and its metabolites were perceived to contribute to its prominent pharmacological activities. Oxyberberine (OBB) is a gut metabolite of BBR, which has been reported to have a superior anti-inflammatory effect in experimental colitis. However, its anti-inflammatory effects against 5-FU-induced IM mice have not yet been investigated. Hence, the purpose of this study was to reveal the protective effects of OBB on IM induced by 5-FU and investigate its potential underlying mechanism. The IM mice model was induced by receiving 5-FU (60 mg/kg, i.p.) for five days. Meanwhile, BBR (50 mg/kg) and OBB (12.5, 25, and 50 mg/kg) were given prior to 30 min intraperitoneal injection of 5-FU for seven days. Results indicated that OBB ameliorated body weight loss, anorexia, diarrhea, and histopathological damage in 5-FU-induced IM mice. After OBB administration, the amounts of MDA, SOD, and GSH altered by IM were remarkably restored. OBB was also observed to dramatically decrease the levels of TNF- α, IL-8, IL-6, COX-2, and iNOS and promote the release of IL-10. Besides, OBB distinctly upregulated the mRNA expressions of PCNA, ZO-1, occludin, and mucin-1, which could improve intestinal homeostasis in IM mice. OBB also blocked the activation of the upstream TLR4/MyD88 signaling pathway, and then it inhibited the phosphorylation of the NF- κ B and MAPK pathways. Importantly, compared with BBR, OBB displayed a superior therapeutic effect to BBR in alleviating 5-FU-induced IM mice. These results indicated that OBB has considerable potential to become a novel candidate drug against IM.